The Effect Of Home Visits and Aromatheraphy On The Level Of Family Independence And The Fulfillment Of Family Health Tasks With Non-Communicable Diseases - Roswita, Ria; Nurhayati, Nurhayati (JURNAL CITRA KEPERAWATAN, 2025)
Non-communicable diseases are the main cause of death in the world. Home visits need to be combined with aromatherapy so that they can increase the effectiveness of the intervention. This study aims to assess the effect of home visits and aromatheraphy on the level of independence and fulfillment of family health tasks with non-communicable diseases. The study was conducted in the Working Area of ​​Martapura 1 Health Center, Banjar Regency. The sample of this study was 20 families with non-communicable diseases selected using purposive sampling techniques. The results of the research analysis showed that home visits and aromatheraphy had an effect on the level of family independence and fulfillment of family health tasks with a p value of 0.00 <0.05. This indicates that the implementation of home visits and aromatheraphy can increase the level of family independence and fulfillment of family health tasks with non-communicable diseases in Indonesia.